Osteoporosis : Diagnosis and Management - Stovall, Dale W. (Chichester, England : Wiley-Blackwell, 2013)
Osteoporosis is a growing major public health problem that impacts many women and men. In the US alone, it is estimated that 10 million Americans have osteoporosis and another 34 million have low bone mass. Both of these conditions put patients at increased risk for fracture. This book takes a "generalist" approach to the challenge of osteoporosis. It is aimed at those specialists, in particular gynecologists, who have regular clinical contact with particularly prone populations, such as menopausal and post menopausal women, who do not have the need for in-depth knowledge of the subject.
Epidemiology and Genetics of Postmenopausal Osteoporosis -- Osteoporosis in Men -- Mechanisms of Bone Remodeling -- Fracture Risk Assessment -- Secondary Causes of Osteoporosis: bone diseases -- Glucocorticoid-induced Osteoporosis -- Secondary Causes of Osteoporosis: Other Medications -- Hormone Therapy for Osteoporosis -- Bisphosphonates -- Denosumab -- Parathyroid Hormone: Anabolic Treatment of Osteoporosis -- Optimum Calcium and Vitamin D for the Prevention and Treatment of Osteoporosis -- The Use of Combination Therapy in the Treatment of Postmenopausal Osteoporosis -- Emerging Therapies -- Monitoring Therapy for Osteoporosis -- Persistence and Compliance with Medications to Prevent Fractures: Epidemiology, Etiology, and Management Issues.
Includes bibliographical references at the end of each chapters and index.
Online resource; title from title page (ebrary, viewed August 1, 2013).
Keywords: Osteoporosis; Osteoporosis -- Diagnosis; Osteoporosis -- Therapy; Risk factors; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Osteoporosis; Osteoporosis -- diagnosis; Osteoporosis -- therapy; Electronic books; Electronic books